Pengembangan Samba Server Sebagai Primary Domain Controller Pada Debian 6.0 Squeeze Studi Kasus : Laboratorium Komputasi Dasar FMIPA Universitas Lampung - Didik Kurniawan; Rhisky Sambayu; Wisnu Wardhana (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
Samba is an application that can connect two different operating system platforms. This application created in order to computer Linux, Unix, or BSD so that can be used as a Samba file server-based protocol, so Windows-based computers can access it. Samba server is implemented in the Laboratory of Computation, FMIPA University of Lampung as a means to facilitate access data or files for instructors, assistants, and practitioners. Using Samba server for file sharing can give problems in accessing, storing, and managing data or files because many users are accessing the system on a computer network so that the database server is messy. Considering these problems, the PDC is required as a file server. One purpose of this paper is to apply the Samba server as a PDC centrally in Laboratory of Computation , FMIPA University of Lampung. Based on test, the Samba server as a PDC has been successfully applied so management, storage, and transmission of data becomes easier, the problem was resolved.